#### Answer

$-10$

#### Work Step by Step

Recall the following rule:
$(\sqrt [3] {x^{3}}=x$
Thus, we obtain:
$2\sqrt[3] {-125}=2\sqrt[3] {(-5)^{3}}=2(-5)=-10$

Published by
Cengage Learning

ISBN 10:
1285194055

ISBN 13:
978-1-28519-405-9

$-10$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.